2021
DOI: 10.3390/ijerph18020589
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Exposure to Aflatoxin B1 in Rats: Alterations in Lipids, Hormones, and DNA Methylation among the Offspring

Abstract: Aflatoxins are toxic compounds produced by molds of the Aspergillus species that contaminate food primarily in tropical countries. The most toxic aflatoxin, aflatoxin B1 (AFB1), is a major cause of hepatocellular carcinoma (HCC) in these countries. In sub-Saharan Africa, aflatoxin contamination is common, and perinatal AFB1 exposure has been linked to the early onset of HCC. Epigenetic programming, including changes to DNA methylation, is one mechanism by which early life exposures can lead to adult disease. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Wankhade et al have shown that this altered gut microbiome in offspring of obese mothers in turn leads to metabolic changes in the offspring (18). Furthermore, several groups have shown that epigenetic changes that happen during the fetal development are passed on from parents to the offspring and modulate the risk for cancer (19)(20)(21). It is likely that these factors also play an important role in the increased risk for HCC in the offspring of obese mothers, besides the regulation of gene expression through specific microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Wankhade et al have shown that this altered gut microbiome in offspring of obese mothers in turn leads to metabolic changes in the offspring (18). Furthermore, several groups have shown that epigenetic changes that happen during the fetal development are passed on from parents to the offspring and modulate the risk for cancer (19)(20)(21). It is likely that these factors also play an important role in the increased risk for HCC in the offspring of obese mothers, besides the regulation of gene expression through specific microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerase chain reaction was used to amplify the region in bisulfite‐converted DNA (15 min at 95°C then [45 cycles × (95°C for 30 s, 43°C for 30 s, 72°C for 1 min)] then 72°C for 10 min). The product was sequenced with a PyroMark Q96 ID according to the procedure previously outlined (Ferrari et al, 2019; Rotimi et al, 2021). Methylation data for three CpG sites on the Alu elements were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Prenatal exposure to AFB 1 reduces the body weight of neonatal rats, disrupts lipid and hormone levels, and affect the methylation levels of p53 and growth-regulator H19 in the liver and serum. The pathological changes may increase the risk of HCC in the offspring ( Rotimi et al, 2021 ). These studies indicate that exposure of sexually mature animals to AFB 1 affects gamete production, gamete quality, and gamete maturation, and AFB 1 also disrupts embryonic development, posing a long-term health threat to both pregnant animal mothers and offspring.…”
Section: Afb 1 -Induced Toxicitymentioning
confidence: 99%